If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 92 = x(x + 4) Reorder the terms: 92 = x(4 + x) 92 = (4 * x + x * x) 92 = (4x + x2) Solving 92 = 4x + x2 Solving for variable 'x'. Reorder the terms: 92 + -4x + -1x2 = 4x + -4x + x2 + -1x2 Combine like terms: 4x + -4x = 0 92 + -4x + -1x2 = 0 + x2 + -1x2 92 + -4x + -1x2 = x2 + -1x2 Combine like terms: x2 + -1x2 = 0 92 + -4x + -1x2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. -92 + 4x + x2 = 0 Move the constant term to the right: Add '92' to each side of the equation. -92 + 4x + 92 + x2 = 0 + 92 Reorder the terms: -92 + 92 + 4x + x2 = 0 + 92 Combine like terms: -92 + 92 = 0 0 + 4x + x2 = 0 + 92 4x + x2 = 0 + 92 Combine like terms: 0 + 92 = 92 4x + x2 = 92 The x term is 4x. Take half its coefficient (2). Square it (4) and add it to both sides. Add '4' to each side of the equation. 4x + 4 + x2 = 92 + 4 Reorder the terms: 4 + 4x + x2 = 92 + 4 Combine like terms: 92 + 4 = 96 4 + 4x + x2 = 96 Factor a perfect square on the left side: (x + 2)(x + 2) = 96 Calculate the square root of the right side: 9.797958971 Break this problem into two subproblems by setting (x + 2) equal to 9.797958971 and -9.797958971.Subproblem 1
x + 2 = 9.797958971 Simplifying x + 2 = 9.797958971 Reorder the terms: 2 + x = 9.797958971 Solving 2 + x = 9.797958971 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 9.797958971 + -2 Combine like terms: 2 + -2 = 0 0 + x = 9.797958971 + -2 x = 9.797958971 + -2 Combine like terms: 9.797958971 + -2 = 7.797958971 x = 7.797958971 Simplifying x = 7.797958971Subproblem 2
x + 2 = -9.797958971 Simplifying x + 2 = -9.797958971 Reorder the terms: 2 + x = -9.797958971 Solving 2 + x = -9.797958971 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = -9.797958971 + -2 Combine like terms: 2 + -2 = 0 0 + x = -9.797958971 + -2 x = -9.797958971 + -2 Combine like terms: -9.797958971 + -2 = -11.797958971 x = -11.797958971 Simplifying x = -11.797958971Solution
The solution to the problem is based on the solutions from the subproblems. x = {7.797958971, -11.797958971}
| a^4b^6/ab^3 | | 5/8x-51/8x=3/2 | | 9x+6(100)= | | 3q-r=7 | | 483575.32=19105.8019x^(5/2)-60446.915x | | 2=9y/4 | | 18=(4/3x)(-3/2x) | | 5/4=z/8 | | 8+6(x-3)=2-7(x-6) | | 4x*2x^2=0 | | 5/4=2/8 | | 20x-(2x-4)=40 | | (4x+7)+(2x-1)=180 | | K-7=-9 | | 3(1-2x)=2(5x-1) | | 5x+20=4x+20 | | 14+6=-4(4x-5) | | 4x-12-3x+9=2x+8 | | 2x(x-6)(3x+2)=0 | | 5a^2+3a-2=0 | | -2.3-3x-4.1-x=-3x-0.9 | | ln(3x-6)=8 | | K+12=10 | | K+10=10 | | 3x-2x+8=5x+5+3 | | -2+n=6n+22 | | -3=-15-3x | | 5a-3=a+45 | | M+22=50 | | K+18=36 | | W+39=39 | | K+21=42 |